To Demonstrate Challenges in Treating Infratentorial Brain Tumors in Pediatrics at the Children’s Hospital and Institute of Child Health, Lahore - Muhammad Shafiq, Shazia Riaz, Safwan Ahmad, Laeeq Ur Rehman, Amber Goraya, Mehvish Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To demonstrate challenges in treating infratentorial Brain tumors in pediatrics at The Children’s Hospital and Institute of Child Health, Lahore Methodology: This Descriptive observational study was done at the Department of Pediatric Hematology & Oncology at CH&UCH Lahore from August 2021 to February 2022. Sixty-four newly diagnosed patients of infra-tentorial tumors were enrolled by using non-probability, consecutive sampling technique. Main variables of study were age, parents education, socioeconomic status, traveling distance, TLS, stagging workup, Histopathology, Treatment, and Outcome . SPSS version 23.1 was used for data analysis. Test of significance was applied taking p value ≤0.05 as significant value. Results: In this study, the mean age of children was 7.14 ± 3.76 years. Out of 64 children, 35 (54.7%) were males and 29 (45.3%) females Forty three (67%) patients belong to rural area and 21 (32%) from urban area. In our study population, Father of 24 (37.5%) patients and mother of 38 (59.37%) patients never attended school. Fifty six (87.5%) patients belong to low income socioeconomic status while 8(12.5%) patients from middle income status. Thirty four (53.12%) patients had a travelled for more than 200KM. Lag time 1 (patient interval) was <2 weeks in 43 (67.2%) cases, and 2-4 weeks in 20 (31.3%) cases. Lag time 2 (referred interval) was noted as <1 Month in 19 (29.7%) cases, and <2 Months in 26 (40.6%) cases. Lag time 3 (treatment interval) was noted in <1 Month in 2 (3.1%) cases, and <2 Months in 6 (9.4%) cases, but in 48 (75.0%) cases lag time 3 was not applicable. Out of 64 cases, cure with Gross Total Resection was noted in 5 (7.8%) cases, residual tumor in 21 (32.8%) and palliation in 37 (57.8%) cases. Practical implication: Conclusion: Advanced disease presentation is common, infra tentorial brain tumors are always challenging and has the least favorable outcomes amongst all pediatric tumors. Delayed diagnosis due to cultural and financial barriers and lack of care at primary health care level and poor referral to oncology units owing to deficient health care system are the major contributory challenges for management and poor outcomes. Keywords: lag time, infra-tentorial tumors, challenges, Pediatrics